Patient Perspectives on the Learning Health System: the Importance of Trust and Shared Decision Making - Kelley, Maureen (Am J Bioeth, 2015)
We conducted focus groups to assess patient attitudes towards research on medical practices in the context of usual care. We found that patients focus on the implications of this research for their relationship with and trust in their physicians. Patients view research on medical practices as separate from usual care, demanding dissemination of information and in most cases, individual consent. Patients expect information about this research to come through their physician, whom they rely on to identify and filter associated risks. In general, patients support this research, but worry that participation in research involving randomization may undermine individualized care that acknowledges their unique medical histories. These findings suggest the need for public education on variation in practice among physicians and the need for a collaborative approach to the governance of research on medical practices that addresses core values of trust, transparency and partnership.